2017
DOI: 10.1021/acs.jmedchem.6b01848
|View full text |Cite
|
Sign up to set email alerts
|

Use of Molecular Modeling to Design Selective NTS2 Neurotensin Analogues

Abstract: Neurotensin exerts potent analgesia by acting at both NTS1 and NTS2 receptors, whereas NTS1 activation also results in other physiological effects such as hypotension and hypothermia. Here, we used molecular modeling approach to design highly selective NTS2 ligands by investigating the docking of novel NT[8-13] compounds at both NTS1 and NTS2 sites. Molecular dynamics simulations revealed an interaction of the Tyr residue of NT[8-13] with an acidic residue (Glu) located in the ECL2 of hNTS2 or with a basic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 37 publications
6
28
0
Order By: Relevance
“…As previously observed (Uhl et al, 1977;St-Pierre et al, 1981;Granier et al, 1982;Lugrin et al, 1991;Held et al, 2013;Fanelli et al, 2017), arginine-to-lysine substitutions at positions 8 and 9 (compound 1) or the insertion of the reduced amine bond between those two residues (2) had no major impact on NTS1/NTS2 receptor binding. As already reported (Doulut et al, 1992;Vivet et al, 2000;René et al, 2013;Fanelli et al, 2015), insertion of the TMSAla residue in position 13 (3) was welltolerated by both receptors, with significantly improved affinity at NTS1 (K i = 0.018 nM), when compared to either 1 or to the native NT(8-13) peptide (220-and 80-fold increase, respectively).…”
Section: Impact Of the Peptide Backbone Modifications On Receptor Binsupporting
confidence: 74%
See 4 more Smart Citations
“…As previously observed (Uhl et al, 1977;St-Pierre et al, 1981;Granier et al, 1982;Lugrin et al, 1991;Held et al, 2013;Fanelli et al, 2017), arginine-to-lysine substitutions at positions 8 and 9 (compound 1) or the insertion of the reduced amine bond between those two residues (2) had no major impact on NTS1/NTS2 receptor binding. As already reported (Doulut et al, 1992;Vivet et al, 2000;René et al, 2013;Fanelli et al, 2015), insertion of the TMSAla residue in position 13 (3) was welltolerated by both receptors, with significantly improved affinity at NTS1 (K i = 0.018 nM), when compared to either 1 or to the native NT(8-13) peptide (220-and 80-fold increase, respectively).…”
Section: Impact Of the Peptide Backbone Modifications On Receptor Binsupporting
confidence: 74%
“…Additionally, we synthesized the NT(8-13) derivatives 7 (H-Lys-Lys-Sip-Tyr-Ile-TMSAla-OH) and 8 (H-Lys [CH 2 NH]Lys-Sip-Tyr-Ile-TMSAla-OH), in which both silylated amino acids were inserted. Previous studies have also revealed that substitution of the Tyr 11 residue could provide a handle controlling NT receptor subtype selectivity (Dubuc et al, 1999;Boules et al, 2010;Einsiedel et al, 2011;Held et al, 2013;Fanelli et al, 2017). Accordingly, compound 9 (H-Lys-Lys-Pro-Lys-Ile-Leu-OH), previously reported in Richelson et al (2008), Einsiedel et al (2011), Fanelli et al (2017), and Magafa et al 2019, showed a significant selectivity in favor to NTS2 (NTS2/NTS1 ratio = 25).…”
Section: Design Of the Nt(8-13) Analogsmentioning
confidence: 81%
See 3 more Smart Citations